Alihkode dan Campur Kode Dalam Tuturan Masyarakat Bumiayu - siti ulfiyani (Universitas Aki, 2014)
Contiguity between Javanese, Sundanese, Indonesian and foreign language substitutions involving indigenous communities and settlers in Bumiayu displays code switching and code mixing symptoms. This study aims at describing a form of both codes and to identify the reasons that cause it. This study used a qualitative descriptive approach. The data of this study is a fragment of a number of conversation events and interviews. The data were processed and analyzed by a contextual approach. Code switching that is found are two, namely external and internal code switching. Based on the language used, there are some variations in the code mixing in Bumiayu speech community, those are mixed with the basic Javanese code, interfered with the basic Sundanese code, and interfered with the basic Indonesian code due to several reasons, namely 1) adjustment of the language, 2) transition topics, 3) learning the language, 4) respect, 5) the presence of a third person, and 6) familiarity. Code mixing in Bumiayu occurs for several reasons, namely, 1) the limited use of the code, 2) the use of more popular terms, 3) evokes sense of humour, and 4) suppression purposes. Key words : code, code switching, code mixing